EVALUASI MUTU BETON MENGGUNAKAN BETON INTI DIAMETER KECIL - Yulius Rakhman (LPPM Universitas Hasanuddin, 2019)
One of the causes of limited sampling on concrete structures is that there are reinforcement in the concrete structure, so that when using a large diameter drill core, can damage the concrete structure. Therefore a study of small diameter concrete was conducted to predict the compressive strength of cylindrical concrete. Test specimens in the form of concrete cylinders with dimension 10 cm x 20 cm, 2 concrete plates with dimension 45cm x 45cm x 13cm and 4 concrete beams with dimensions 70 cm x 30 cm x 15 cm by taking concrete using a drill core diameter of 2